2013
DOI: 10.1063/1.4799199
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the discharge current behavior in reactive high power impulse magnetron sputtering of oxides

Abstract: The discharge current behavior in reactive high power impulse magnetron sputtering (HiPIMS) of Ti-O and Al-O is investigated. It is found that for both metals, the discharge peak current significantly increases in the oxide mode in contrast to the behavior in reactive direct current magnetron sputtering where the discharge current increases for Al but decreases for Ti when oxygen is introduced. In order to investigate the increase in the discharge current in HiPIMS-mode, the ionic contribution of the discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
61
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 32 publications
11
61
1
Order By: Relevance
“…However, Aiempanakit et al [17] stated that the large discharge current in oxide mode are mainly attributed to the large ionic current due to the impingement of a high fraction of O 1+ ions. Hala et al [18] have shown a peak current dependency on the pulse frequency, in which a higher peak current was recorded at lower pulse frequency.…”
Section: Introductionmentioning
confidence: 99%
“…However, Aiempanakit et al [17] stated that the large discharge current in oxide mode are mainly attributed to the large ionic current due to the impingement of a high fraction of O 1+ ions. Hala et al [18] have shown a peak current dependency on the pulse frequency, in which a higher peak current was recorded at lower pulse frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Measured energies of reactive gas ions in HiPIMS discharges suggest that the ions originate from the target surface rather than from the gas phase. 20 It is therefore important to determine the partial sputtering yield of the reactive gas from the target surface to evaluate the contribution of sputtering to the total reactive gas ion flux.…”
mentioning
confidence: 99%
“…An increased voltage for a constant current leads to a higher average powers. Since a pulsed voltage is used another phenomenon also arises when oxygen is added to the sputtering process of titanium, and that is that the peak current value increases for a constant average current [26].…”
Section: Reactive Sputteringmentioning
confidence: 99%